MENGUBAH TANTANGAN MENJADI PELUANG: MANAJEMEN PENDIDIKAN ISLAM DALAM LITERASI TEKNOLOGI DAN PENDIDIKAN KARAKTER DI TENGAH ARUS MODERNISASI - Nur Hafidz Firmansyah; Siti Aimah (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
Modernization has had a significant impact on various aspects of life, including the world of education. In the context of Islamic education, modernization poses major challenges, especially in terms of adaptation to technology, globalization, and changes in social values. Islamic educational institutions must face the dualism between maintaining traditional values and meeting the demands of the times. This study aims to identify the challenges faced by Islamic educational institutions, especially at MTs Negeri 8 Banyuwangi, and how these challenges can be turned into opportunities. The focus of this study includes technological literacy in Islamic education, character development of students, and management of Islamic educational institutions in the midst of modernization. Through a qualitative approach and case studies, this study found that the use of technology such as online classes and Islamic learning applications can improve the quality of education without sacrificing Islamic values. In addition, character education is an important element in forming individuals who are intellectually intelligent and have noble morals. The integration of technological literacy with character education, as well as the application of Islamic principles in educational management, is believed to be able to create a globally competitive generation without losing their spiritual identity. This study provides an important contribution in formulating practical solutions for Islamic educational institutions to optimize the potential of modernization while maintaining the integrity of religious values.